AB0584 Clinical Features of Patients with Henoch-SchÖNlein Purpura. (10th June 2014) - Loricera, J.; Calvo-Río, V.; Mata, C.; Martín, L.; Ortiz-Sanjuán, F.; Santos-Gόmez, M.; Άlvarez, L.; González-Vela, M.C.; González-Lamuño, D.; Rueda-Gotor, J.; Fernández-Llaca, H.; González-Lόpez, M.A.; et al.
Abstract : Background: The severity of clinical features and the outcome in the different series of patients with Henoch-Schönlein Purpura (HSP) shows great variability, probably due to selection-bias. Objectives: Our aim was to establish the actual clinical spectrum of HSP in all age groups using an unselected and wide series of patients diagnosed at a single center. Methods: For this purpose, we performed a retrospective review of 417 patients classified as having HSP according to the criteria proposed by Michel et al. 1 Results: From this series of 417 patients, 240 were men and 177 women with a median age at the time of disease diagnosis of 7.5 years (interquartile range-IQR: 5.3-20.1). Three-quarters of them were children or young people 20 years old and younger (n=315) and a quarter (n=102) were adults. The most frequent precipitating events were a previous infection (38%), usually an upper respiratory tract infection, and/or drug intake (18.5%) shortly before the onset of the vasculitis. At disease onset the most common manifestations were skin lesions (55.9%), nephropathy (24%) gastrointestinal involvement (13.7%), joint symptoms (9.1%), and fever (6.2%). Cutaneous involvement occurring in all the cases, mainly purpuric skin lesion, was the most common manifestations when the vasculitis was fully established, followed by gastrointestinal (64.5%), joint (63.1%), and renal involvement (41.2%).The main laboratory data were leukocytosis (36.7%), anemia (8.9%) and increased of serum IgA levels (31.7%). The most frequent therapies used were corticosteroids (35%), nonsteroidal anti-inflammatory drugs (14%), and cytotoxic agents (5%). After a median follow-up of 12 (IQR: 2-38) months, complete recovery was observed in most cases (n=346; 83.2%) while persistent, usually mild, nephropathy was observed in 32 (7.7%) cases. Relapses were observed in almost a third of patients (n=133; 31.9%). Conclusions: In conclusion, although HSP is a typical vasculitis affecting children and young people, it is not uncommon in adults. The prognosis is favorable in most cases depending mostly on renal involvement. References: Michel BA, Hunder GG, Bloch DA, Calabrese LH. Hypersensiviti vasculitis and Henoch-Schönlein purpura: a comparison between the two disorders. J Rheumatol. 1992; 19:721-728. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4358